Water-soluble unit dose articles
Patent Information
- Application Number
- JP2026053139
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-01
- Filing Date
- 2026-03-27
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167590000001 
Figure 2026167590000002 
Figure 2026167590000003
Abstract
Description
[Technical Field]
[0001] A water-soluble unit-dose article made from a water-soluble film containing a water-soluble polymer, wherein the water-soluble polymer is i) Alginate and, ii) A water-soluble unit-dose article comprising a blend with a caseinate polymer. [Background technology]
[0002] The development of water-soluble films is attracting significant attention in various industries, including packaging, pharmaceuticals, and household goods. These films offer a convenient method for delivering active ingredient doses while reducing the environmental impact associated with conventional packaging materials.
[0003] Conventional water-soluble films often face compatibility issues with various detergent compositions, particularly liquid detergent compositions. Many commercially available detergents contain surfactants, organic solvents, and other chemicals that can negatively interact with synthetic films, such as excessive plasticization, leading to film degradation or reduced integrity. This incompatibility can result in premature dissolution, loss of function, and reduced shelf life.
[0004] While some existing water-soluble films exhibit good solubility and dissolution rate, they often lack mechanical strength and durability. This limitation affects their handling, transport, and application, potentially making them unsuitable for products requiring robust packaging solutions. During the manufacture of detergent pouches, the film must be manipulated and sealed. High elongation at the breaking point allows the film to withstand the mechanical stresses during manufacturing without compromising its integrity.
[0005] In the field of water-soluble films, polyvinyl alcohol (PVA) is widely used due to its desirable properties, including good film-forming ability, water solubility, and mechanical strength. However, while PVA-based films have been successful in various applications, there is a need to find alternative films made from natural materials that exhibit good compatibility with detergent compositions and good mechanical strength and durability. [Overview of the project] [Means for solving the problem]
[0006] A first aspect of the present invention is a water-soluble film, the water-soluble film comprising a water-soluble polymer, the water-soluble polymer comprising a blend of an alginate and a caseinate polymer.
[0007] Surprisingly, the film according to the present invention was found to exhibit good compatibility with detergent compositions, particularly liquid detergent compositions, and superior mechanical properties compared to alginate films or caseinate polymer films.
[0008] The present invention relates to a water-soluble unit-dose article comprising a water-soluble film. The water-soluble film comprises a water-soluble polymer, the water-soluble polymer comprising a blend of alginate and caseinate polymers. Surprisingly, the film according to the present invention has been found to exhibit good compatibility with detergent compositions, particularly liquid detergent compositions, and superior mechanical properties that are better than those of alginate films or caseinate polymer films. The water-soluble unit-dose article according to the present invention comprises a treatment composition and at least one internal compartment, the treatment composition being contained within the at least one compartment. The treatment composition is selected from laundry detergent compositions, laundry softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof. [Modes for carrying out the invention]
[0009] Water-soluble film The water-soluble film contains a water-soluble polymer, which includes a blend of alginate and caseinate polymers. The alginate and caseinate polymers are described in more detail below.
[0010] The water-soluble film of the present invention is water-soluble. The water-soluble film preferably has a thickness of 30 μm to 150 μm, preferably 50 μm to 100 μm, and most preferably 60 μm to 85 μm.
[0011] Characteristics of water-soluble films: The water-soluble film preferably has a dissolution time of less than 90 seconds, preferably less than 60 seconds, and more preferably less than 30 seconds at 10°C and a thickness of about 76 micrometers, as measured according to MonoSol Test Method 205 (MSTM 205), as described in U.S. Patent No. 7,022,656, column 8, lines 10-57. Preferably, the water-soluble film has a dissolution time of less than 300 seconds, preferably less than 200 seconds, and more preferably less than 180 seconds at 5°C and a thickness of about 76 micrometers, as measured according to MonoSol Test Method 205 (MSTM 205). Preferably, the disintegration time of the film at a thickness of about 76 microns is less than or equal to about 40 seconds or less, or less than or equal to about 30 seconds, as measured according to MonoSol Test Method 205 (MSTM 205), at a temperature of 10°C. More preferably, the disintegration time of the film at a thickness of approximately 76 microns is approximately 120 seconds or less, or approximately 80 seconds or less, at a temperature of 5°C, as measured according to MonoSol Test Method 205 (MSTM 205).
[0012] The film collapse time (I) and film dissolution time (S) may be corrected to a reference or standard film thickness (76 microns) using the exponential algorithms shown in Equations 1 and 2 below, respectively. Icorrected = Imeasured × (reference thickness) 2 / Measurement thickness 2 ) Scorrected = Smeasured × (Reference thickness) 2 / Measurement thickness 2 )
[0013] Generally, a higher tensile strength value is desirable because it results in a tougher water-soluble unit-dose article. A higher e modulus is desirable from the viewpoint of providing water-soluble unit-dose articles that have higher rigidity and are less likely to deform and stick together when stacked and loaded with each other during manufacturing. Preferably, when measured at 23°C and 40%RH, the water-soluble film has a tensile strength or stress at break of at least 20 N / mm², preferably 20 N / mm² to 80 N / mm², more preferably 25 N / mm² to 80 N / mm², a modulus at 10% elongation of at least about 20 N / mm², and a stress at 100% elongation of at least 12 N / mm². Furthermore, when measured according to the same method, the water-soluble film has a tensile strain at break of about 25% to about 1600%, preferably 50% to 1200%, more preferably about 75% to about 800%. When measured at 100°C and 40%RH, water-soluble films have a tensile strain at break of at least about 50% when measured according to the same method.
[0014] Preferably, the water-soluble film and / or water-soluble polymer resin and / or individual water-soluble polymers have a biodegradation rate of at least 60%, preferably at least 65%, more preferably at least 70% after 60 days, or at least 60%, preferably at least 65%, more preferably at least 70% after 28 days, according to the OECD 301B test.
[0015] Preferably, the water-soluble film has a glass transition temperature of less than -5°C and a melting transition temperature of more than 80°C, as measured by the DSC standard procedure.
[0016] Water-soluble films may be further plasticized upon contact with liquid detergent compositions, resulting in swelling of the water-soluble film (positive film swelling value). Alternatively, water-soluble films may also be deplasticized upon contact with liquid detergent compositions, resulting in deswelling of the water-soluble film. Negative film swelling values may result in brittle films during product aging, while film swelling values exceeding 15% may make the entire unit-dose article flexible during aging, and therefore aesthetically unattractive. Preferably, the film swelling value is -15% to 15%, more preferably 0% to 15% or 5% to 15%.
[0017] Preferably, the weight ratio of the alginate and caseinate polymer is 90:10 to 10:90, more preferably 75:25 to 25:75.
[0018] The water-soluble polymer may be present in the film at a concentration of 50% to 95% by weight, preferably 55% to 90% by weight, and more preferably 60% to 80% by weight.
[0019] Preferably, the water-soluble film comprises a non-aqueous plasticizer. Preferably, the non-aqueous plasticizer is selected from polyols, sugar alcohols, and mixtures thereof. Suitable polyols include polyols selected from the group consisting of glycerol, diglycerin, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol with a molecular weight of 400 or less, neopentyl glycol, 1,2-propylene glycol, 1,3-propanediol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane and polyether polyols, or mixtures thereof. Suitable sugar alcohols include sugar alcohols selected from the group consisting of isomalt, maltitol, sorbitol, xylitol, erythritol, adonitol, dulcitol, pentaerythritol, and mannitol, or mixtures thereof. More preferably, the non-aqueous plasticizer is selected from glycerol, 1,2-propylene glycol, dipropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, triethylene glycol, polyethylene glycol, sorbitol, or mixtures thereof, and most preferably, is selected from glycerol, sorbitol, trimethylolpropane, dipropylene glycol, and mixtures thereof. One particularly suitable plasticizer system comprises a blend of glycerol, sorbitol, and 2-ethyl-2-hydroxymethyl-1,3-propanediol. Another particularly suitable plasticizer system comprises a blend of glycerin, dipropylene glycol, and sorbitol. Preferably, the film comprises 5% to 50% by weight, preferably 10% to 40% by weight, more preferably 20% to 30% by weight of the non-aqueous plasticizer, based on the total weight of the film.
[0020] Preferably, the water-soluble film according to the present invention contains a surfactant. Preferably, the water-soluble film contains 0.1% to 5% by weight, preferably 1% to 3% by weight, of the surfactant. Suitable surfactants include nonionic, cationic, anionic, amphoteric, and bipolar types. Suitable surfactants include, but are not limited to, polyoxyethylene-modified polyoxypropylene glycol, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylene glycol and alkanolamides (nonionic substances), polyoxyethylene-modified amines, quaternary ammonium salts and quaternized polyoxyethylene-modified amines (cationic substances), and amine oxides, N-alkyl betaines and sulfobetaines (bipolar substances). Other suitable surfactants include sodium dioctyl sulfosuccinate, lactyl fatty acid esters of glycerol and propylene glycol, lactyl esters of fatty acids, sodium alkyl sulfate, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, acetylated esters of fatty acids, and combinations thereof.
[0021] Preferably, the water-soluble film according to the present invention contains a lubricant / release agent. Suitable lubricants / release agents include, but are not limited to, fatty acids and their salts, aliphatic alcohols, fatty acid esters, aliphatic amines, aliphatic amine acetates, and fatty acid amides. Preferred lubricants / release agents are fatty acids, fatty acid salts, and aliphatic amine acetates. Preferably, the amount of lubricant / release agent in the water-soluble film is in the range of 0.02% to 1.5% by weight of the water-soluble film, preferably 0.1% to 1% by weight.
[0022] Preferably, the water-soluble film comprises a filler, spreading agent, anti-tacking agent, tack remover, or a mixture thereof. Suitable fillers, spreading agents, anti-tacking agents, tack removers, or mixtures thereof include, but are not limited to, starch, modified starch, crosslinked polyvinylpyrrolidone, crosslinked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica. Preferred materials are starch, modified starch, and silica. Preferably, the amount of the filler, spreading agent, anti-tacking agent, tack remover, or mixture thereof in the water-soluble film ranges from 0.1 wt% to 25 wt% of the water-soluble film, preferably from 1 wt% to 10 wt%, more preferably from 2 wt% to 8 wt%, and most preferably from 3 wt% to 5 wt%. In the absence of starch, one preferred range of the suitable filler, spreading agent, anti-tacking agent, tack remover, or mixture thereof is 0.1 wt% to 1 wt% of the water-soluble film, preferably 4 wt%, more preferably 6 wt%, even more preferably 1 wt% to 4 wt%, and most preferably 1 wt% to 2.5 wt%.
[0023] Preferably, the water-soluble film according to the present invention has a residual moisture content of at least 4 wt% of the water-soluble film, more preferably in the range of 4 wt% to 15 wt%, even more preferably 5 wt% to 10 wt%, as measured by Karl Fischer titration. The film was pre-conditioned for 24 hours at a temperature of 20°C and 60% relative humidity prior to determining the residual moisture content.
[0024] Preferably, the water-soluble film according to the present invention comprises aversive agent, preferably a bittering agent. Suitable bittering agents include, but are not limited to, naringin, sucrose octaacetate, quinine hydrochloride, denatonium benzoate, or mixtures thereof. Any suitable concentration of the aversive agent may be used in the film. Suitable levels include, but are not limited to, 1 ppm to 5000 ppm, or even 100 ppm to 2500 ppm, or even 250 ppm to 2000 ppm, relative to the water-soluble film.
[0025] The water-soluble film according to the present invention may be opaque, transparent, or translucent. The water-soluble film according to the present invention may include a printable area. The printable area can be obtained using standard techniques such as flexographic printing or inkjet printing.
[0026] The water-soluble film or water-soluble unit-dose article or both according to the present invention may be coated with a lubricant. Preferably, the lubricant is selected from talc, zinc oxide, silica, siloxane, zeolite, silicic acid, alumina, sodium sulfate, potassium sulfate, calcium carbonate, magnesium carbonate, sodium citrate, sodium tripolyphosphate, potassium citrate, potassium tripolyphosphate, calcium stearate, zinc stearate, magnesium stearate, starch, modified starch, clay, kaolin, gypsum, cyclodextrin, or mixtures thereof.
[0027] Alginate Alginates are naturally occurring polysaccharides derived from the cell walls of brown algae (Phaeophyceae), particularly species of the genera Laminaria and Ascophyllum in the Laminariaceae family. They are composed of two monomer units: β-D-mannuronic acid (M) and α-L-guluronic acid (G), which are arranged in various sequences and proportions, resulting in the formation of homopolymer blocks (GG or MM) and heteropolymer blocks (MG). Alginates are widely recognized for their unique properties, including gel-forming ability, biocompatibility, and biodegradability, making them an attractive material for a variety of applications, including food, pharmaceuticals, and biodegradable films.
[0028] Alginates are linear copolymers, and their properties may be influenced by the ratio of M blocks to G blocks. The presence of G blocks allows for ionic crosslinking of calcium ions (Ca 2+ This contributes to the performance of alginates that form gels in the presence of divalent cations such as ).
[0029] Alginates are soluble in water, especially under alkaline conditions, and form viscous solutions. This solubility is important for their application in water-soluble films because it allows for easy processing and film formation.
[0030] The ability of alginates to gel upon the addition of calcium ions or other divalent cations is a key characteristic. This gelation mechanism can be utilized to create films exhibiting controlled release properties, which are suitable for encapsulating active ingredients or detergents.
[0031] Alginates are biodegradable, breaking down into non-toxic by-products, which aligns with the growing demand for sustainable materials.
[0032] The synergistic effect between alginate polymer and caseinate polymer improves the overall performance of water-soluble films and addresses compatibility issues with detergent compositions. It also exhibits improved mechanical strength, particularly in its elongation properties.
[0033] Caseinate polymer Casein is a milk-derived protein that is relatively insoluble in water. It is often obtained by precipitation after the addition of an acid to milk (caseic acid) or rennet (rennet casein). Caseinates are salts of casein; typically defined as its counterions selected from the group consisting of calcium, potassium, ammonium, magnesium, and sodium, or mixtures thereof, most preferably sodium.
[0034] The water-soluble film according to the present invention comprises a water-soluble polymer including a blend of a caseinate polymer and an alginate, wherein the caseinate polymer is preferably selected from alkali metal salts of caseinate, and more preferably sodium caseinate.
[0035] The polymer according to the present invention is stated to contain caseinate, but in practice, this caseinate is a mixture of caseinate and casein impurities. The relative weight ratio of casein impurities to caseinate is a function of the pH of the water-soluble film. Therefore, when caseinate is referred to herein, it includes levels of pure sodium caseinate as well as casein impurities.
[0036] Although not bound by theory, casein consists of a(s1)-casein, a(s2)-casein, β-casein, and κ-casein. Like any protein, casein is composed of hundreds of individual amino acids, each of which can have a positive or negative charge depending on the pH of the surrounding system. At a certain pH value, all positive and negative charges on casein remain in equilibrium (i.e., the net charge on the protein is 0), and this pH value is known as the isoelectric point (IEP), which for casein is 4.6. The IEP is the pH at which the protein is poorly soluble. Therefore, to make casein soluble, alkaline conditions are used, and it is used in the form of caseinate.
[0037] Preferably, the water-soluble polymer is present in 60% to 80% by weight of the water-soluble film according to the present invention and consists of a mixture of alginate and caseinate polymers.
[0038] Film manufacturing method The water-soluble films according to the present invention may be formed by mixing and co-casting alginate and caseinate polymers in a casting solution with preferred and optional secondary additives as described herein, according to the types and amounts described herein. When the polymers are first mixed, the water-soluble film is preferably formed by casting the resulting mixture (e.g., together with other plasticizers and other additives) to form a film. Another embodiment features a water-soluble film formed by extrusion, e.g., blown extrusion. Most preferably, the water-soluble films according to the present invention are prepared by solution casting.
[0039] Water-soluble unit dose articles The present invention relates to a water-soluble unit-dose article comprising a water-soluble film as described herein, a treatment composition, and at least one internal compartment, wherein the treatment composition is contained within at least one compartment. The treatment composition will be described in more detail below.
[0040] A water-soluble unit-dose article includes a water-soluble film molded to contain at least one internal compartment surrounded by a water-soluble film. The unit-dose article may include a first water-soluble film and a second water-soluble film sealed together to define the internal compartment. The water-soluble unit-dose article is configured to prevent the treatment composition from leaking out of the compartment during storage. However, when the water-soluble unit-dose article is added to water, the water-soluble film dissolves, releasing the contents of the internal compartment into the washing solution.
[0041] A compartment should be understood as a sealed internal space within a unit-dose article that holds the detergent composition. During manufacturing, the first water-soluble film may be shaped to include an opening compartment to which the treatment composition is added. Next, the first film is covered with a second water-soluble film in an orientation that closes the opening of the compartment. The first and second films are then sealed together along the sealing region. Sealing can be performed after solvent sealing, heat sealing, or a combination thereof. A preferred sealing solvent is water.
[0042] A unit dose article may contain one or more compartments, more than two compartments, or more than three compartments. The compartments may be arranged in an overlapping orientation, that is, one on top of the other. In such an orientation, the unit dose article contains three films: top, middle, and bottom. Alternatively, the compartments may be positioned in a side-by-side orientation, that is, one adjacent to the other. The compartments may also be oriented in a "tire and rim" arrangement, that is, the first compartment is positioned adjacent to the second compartment, but the first compartment at least partially surrounds the second compartment but does not completely enclose it. Alternatively, one compartment may be completely enclosed within another compartment.
[0043] If a unit-dose article contains at least two compartments, one of the compartments may be smaller than the other. If a unit-dose article contains at least three compartments, two of the compartments may be smaller than a third compartment. If a unit-dose article contains at least four compartments, at least three of the compartments may be smaller than a fourth compartment, preferably with the smaller compartments overlapping the larger compartments. The overlapping compartments are preferably oriented adjacent to each other.
[0044] Preferably, the water-soluble unit-dose article comprises at least two compartments, preferably at least three compartments, and more preferably at least four compartments, and most preferably, the water-soluble unit-dose article comprises a first compartment, at least a second compartment superimposed on the first compartment, more preferably at least a third compartment oriented adjacent to the second compartment (with the second and third compartments superimposed on the first compartment), and even more preferably at least a fourth compartment oriented adjacent to the second and third compartments (with the second, third, and fourth compartments superimposed on the first compartment).
[0045] In a multi-compartment orientation, the detergent composition may be contained in at least one of the compartments. For example, the detergent composition may be contained in only one compartment, or in two compartments, or even three compartments, or even all of the available compartments.
[0046] Each section may contain the same composition or different compositions. The different compositions may all be in the same form or in different forms.
[0047] The water-soluble unit-dose article may contain at least two internal compartments, and the detergent composition may be contained in at least one of these compartments. Preferably, the unit-dose article may contain at least three compartments, and the detergent composition may be contained in at least one of these compartments.
[0048] A water-soluble unit-dose article according to the present invention may comprise at least one water-soluble film according to the present invention. Alternatively, a water-soluble unit-dose article according to the present invention may comprise at least two or even at least three water-soluble films according to the present invention. Alternatively, a water-soluble unit-dose article according to the present invention may comprise only the water-soluble films according to the present invention, i.e., it may not comprise any water-soluble films outside the scope of the present invention. Preferably, a water-soluble single-compartment unit-dose article or a water-soluble multi-compartment unit-dose article with multiple adjacent compartments is prepared, where both the lower and upper water-soluble films enclosing the individual compartments are water-soluble films according to the present invention. Alternatively, either the upper or lower water-soluble film is according to the present invention. A water-soluble unit-dose article having compartments in an overlapping configuration may be prepared. In this configuration, each of the upper, lower, and central water-soluble films may be a water-soluble film according to the present invention. Alternatively, one film, for example, only the central water-soluble film, or only the upper water-soluble film, or only the lower water-soluble film, or any combination of these water-soluble films, may be a water-soluble film according to the present invention, while the remaining water-soluble films are outside the scope of the present invention. Preferably, all water-soluble films contained within a water-soluble unit dose article are water-soluble films according to the present invention. These water-soluble films according to the present invention may be chemically and physically the same, or they may be chemically and / or physically different. "Different" means that the first water-soluble film has at least one chemical and / or physical characteristic that is different from the second water-soluble film. This characteristic can be obtained by selecting different polymer resins, e.g., the average viscosity of the individual polymer solutions, the average degree of hydrolysis of the individual polymers, the ratio of the first water-soluble polymer to the second water-soluble polymer, or a mixture thereof, of different polymer resins. The "target average" takes into account the standard polymer variability inherent in any manufacturing method. Alternatively, this characteristic can also be obtained by changing the relative content of individual components within the water-soluble film, such as polymer resins, with respect to the plasticizer content or water content, or by changing the precise chemical properties of additives.
[0049] "Different" characteristics are evaluated for the starting film before deformation, and differences in water-soluble film content as a result of the deformation process, exchange of active substances between the film and the detergent composition resulting from exposure to the encapsulated detergent composition, and exchange of active substances with the surrounding storage environment are excluded in this evaluation.
[0050] Processing composition The treatment composition may be selected from laundry detergent compositions, laundry softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof, preferably a laundry detergent composition, and preferably a liquid, powder, or mixture thereof, preferably a liquid composition.
[0051] The term "liquid" includes gels, solutions, suspensions, pastes, or mixtures thereof.
[0052] In this specification, "powder" means that the treatment composition may contain solid particles or may be a single homogeneous solid. Preferably, the powder treatment composition contains particles. This means that the powder treatment composition contains individual solid particles, and does not mean that the solid is a single homogeneous solid. The particles may be free-flowing or compressed, and are preferably free-flowing.
[0053] Preferably, the treatment composition is a laundry detergent composition, most preferably a liquid laundry detergent composition.
[0054] The laundry detergent composition can be used in hand washing operations or in automatic machine washing operations, and is preferably used in automatic machine washing operations.
[0055] Preferably, the treatment composition contains a non-soap surfactant, and the non-soap surfactant includes an anionic non-soap surfactant and a nonionic surfactant. Preferably, the treatment composition contains 10% to 60% by weight, more preferably 20% to 55% by weight, of the non-soap surfactant.
[0056] The weight ratio of the non-soap anionic surfactant to the nonionic surfactant may be 1:1 to 20:1, preferably 1.25:1 to 17.5:1, 1.5:1 to 15:1, 1.75:1 to 13:1, or 2:1 to 10:1.
[0057] Preferably, the non-soap anionic surfactant comprises linear alkylbenzene sulfonate, alkyl sulfate, or a mixture thereof. The weight ratio of the linear alkylbenzene sulfonate to the alkyl sulfate is 1:2 to 9:1, preferably 1:1 to 7:1, more preferably 1:1 to 5:1, and most preferably 1:1 to 4:1.
[0058] Exemplary linear alkylbenzene sulfonates are C 10 to C 16 alkylbenzene sulfonic acids or C 11 to C 14 alkylbenzene sulfonic acids. As used herein, "linear" means that the alkyl group is linear. Alkylbenzene sulfonates are well known in the art.
[0059] The alkyl sulfate anionic surfactant may comprise an alkoxylated alkyl sulfate, a non-alkoxylated alkyl sulfate, or a mixture thereof. The alkoxylated alkyl sulfate anionic surfactant is preferably an ethoxylated alkyl sulfate anionic surfactant.
[0060] The alkyl sulfate anionic surfactant may comprise an ethoxylated alkyl sulfate anionic surfactant, which preferably has a molar average degree of ethoxylation of 1 to 5, more preferably 1 to 3, and most preferably 2 to 3.
[0061] The alkyl sulfate anionic surfactant may contain non-ethoxylated alkyl sulfates and ethoxylated alkyl sulfates, and the molar average degree of ethoxylation of the alkyl sulfate anionic surfactant is 1 to 5, more preferably 1 to 3, and most preferably 2 to 3.
[0062] The alkyl fraction of the alkyl sulfate anionic surfactant can preferably be derived from an aliphatic alcohol, an oxo-synthetic alcohol, a Guerbet alcohol, or a mixture thereof.
[0063] Preferably, the treatment composition contains 10% to 50% by weight, more preferably 15% to 45% by weight, even more preferably 20% to 40% by weight, and most preferably 30% to 40% by weight of a non-soap anionic surfactant.
[0064] Preferably, the nonionic surfactant is selected from alcohol alkoxylates, oxo-synthetic alcohol alkoxylates, Guerbet alcohol alkoxylates, alkylphenol alcohol alkoxylates, or mixtures thereof.
[0065] The treatment composition preferably contains 0.01% to 25% by weight, preferably 1% to 22.5% by weight, more preferably 5% to 20% by weight, and most preferably 8% to 20% by weight of a nonionic surfactant.
[0066] Preferably, the treatment composition comprises 0.5% to 20% by weight, more preferably 1% to 15% by weight, even more preferably 1.5% to 10% by weight, and most preferably 2% to 8% by weight of soap, preferably a fatty acid salt, more preferably an amine-neutralized fatty acid salt, wherein the amine is preferably an alkanolamine, more preferably selected from monoethanolamine, diethanolamine, triethanolamine, or a mixture thereof, and more preferably monoethanolamine.
[0067] Preferably, the treatment composition is a liquid treatment composition, and more preferably, the liquid treatment composition contains less than 15% by weight, more preferably less than 13% by weight, even more preferably 1% to 12% by weight, and most preferably 5% to 12% by weight of water.
[0068] Preferably, the treatment composition is a liquid treatment composition comprising a non-aqueous solvent selected from 1,2-propanediol, dipropylene glycol, tripropylene glycol, glycerol, sorbitol, polyethylene glycol, or mixtures thereof. Preferably, the liquid treatment composition contains 10% to 40% by weight, preferably 15% to 30% by weight, of the non-aqueous solvent.
[0069] Preferably, the treatment composition contains a fragrance.
[0070] Preferably, the treatment composition includes auxiliary components selected from the group comprising enzymes, citrates, bleaching agents, bleaching catalysts, dyes, hue dyes, whitening agents, cleaning polymers containing alkoxylated polyamines and polyethyleneimines, stain-releasing polymers, surfactants, solvents, color transfer inhibitors, chelating agents, encapsulated fragrances, polycarboxylates, structuring agents, pH adjusters, and builders containing mixtures thereof.
[0071] Those skilled in the art will be able to envision, using known knowledge and techniques, how to formulate and prepare suitable treatment compositions. Treatment compositions may include common detergent components, such as surfactants, polymers, bleaches, enzymes, fragrances, dyes, structuring agents, fillers, water, or mixtures thereof.
[0072] Those skilled in the art will be familiar with known techniques for manufacturing water-soluble unit-dose articles according to the present invention. [Examples]
[0073] The mechanical properties (elongation at break %) and treatment composition (laundry detergent composition)-film interaction (swelling %) profiles of three bio-based water-soluble films are defined according to the test methods described herein. Film 1 is based on a water-soluble sodium caseinate polymer. Film 2 is based on a water-soluble sodium alginate polymer. Film 3 is based on a 50 / 50 weight blend of sodium caseinate and sodium alginate polymers. The data summarized in Table 1 show that blending the two polymers together results in improved elongation and treatment composition-film interaction behavior. For example, the sodium caseinate film cannot be used in the manufacture of water-soluble liquid detergent articles due to its solubility in detergent compositions, and the sodium alginate film cannot be used because it is not deformable. However, the blended film exhibits both a good detergent composition-film compatibility profile and deformability into unit-dose articles.
[0074] [Table 1] * The film dissolves in the treatment composition and is therefore unmeasurable. ** If the film is too brittle, it will break when the solution belt is removed, and therefore, the swelling percentage cannot be measured for the film area required for this test.
[0075] Water-soluble film manufacturing method A 100 wt% active alginate or caseinate polymer or a 50 / 50 blend solution (sodium alginate from VWR, sodium caseinate from Thermoscientific) was prepared in desalted water containing 27% glycerol per weight of polymer. The solution was homogenized at 70°C for at least 4 hours and left overnight at room temperature to allow degassing before casting. The solution was poured in thin layers onto a PET casting plate through a film applicator with a wet gap ranging from 250 μm to 350 μm and dried overnight at room temperature and 35% rH. The resulting film contained 66 wt% water-soluble polymer resin, 28 wt% glycerol plasticizer system, and 6% water. Individual film thicknesses are summarized in Table 2 below.
[0076] [Table 2] *** The film is too brittle; it breaks when the solution belt is removed, making measurement impossible.
[0077] Swelling % test: Processing composition The following liquid laundry detergent compositions were used to evaluate the swelling percentage of the film.
[0078] [Table 3] * Lutensol FP620 - Ethoxylated Polyethyleneimine (PEI600 EO20) manufactured by BASF ** Lutensit Z96 (a zwitterionic polyamine-zwitterionic hexamethylenediamine manufactured by BASF, 100% of which is quaternized, and about 40% of the polyethoxy (EO24) groups are sulfonated, preferably having the following structure).
[0079] [ka]
[0080] 11cm x 12cm water-soluble film samples were prepared and exposed to the test treatment composition. 750mL of this test liquid treatment composition was required for each test film. The bottom of a clean, inert glass container was covered with a thin layer of liquid, and the first film to be tested was spread on top of the liquid. Any trapped air bubbles beneath the film were gently pushed to the sides. A thin layer of liquid was spread over the first film sample, followed by the second film sample. This process was repeated until five film samples were stacked with thin layers of liquid in between. Next, the remaining liquid was gently poured onto the top of the fifth film so that the film was fully immersed in the liquid. The film was kept wrinkle-free, and no air bubbles were allowed to come into contact with the film. The films were stored in a sealed container under conditions of 50°C for 5 days and 21°C overnight, while still in contact with the liquid. A separate glass container was used for each different film to be tested. The films were then removed from the storage containers, and any excess liquid was removed from the films. A sheet of paper was placed on top of the film, which was then placed on the bench paper. The film was then thoroughly wiped dry with dry paper, such as a dry tissue that did not contain any fibers that could adhere to the film surface. The weight of the film was measured before and after the immersion test, and the relative weight increase / loss was calculated and expressed as a percentage change according to the following formula.
[0081] Change % = (Final weight - Starting weight / Starting weight) * 100. The average value of five film samples per test solution was calculated and reported.
[0082] A negative film swelling value may result in a brittle film during product aging, while a film swelling value exceeding 15% may make the unit-dose article flexible during aging, and therefore aesthetically unattractive. Preferably, the film swelling value is between 0% and 15%.
[0083] Breaking point elongation % test The procedure includes determining the % elongation at break according to ASTM D882 ("Standard Test Method for Tensile Properties of Thin Plastic Sheeting") or an equivalent. An INSTRON tensile testing apparatus (Model 5544 tensile testing machine or equivalent) is used to collect film data. The tests are performed in a standard laboratory atmosphere of 23±2.0℃ and 35±5% relative humidity. At least three test specimens are cut from each using a reliable cutting tool to ensure dimensional stability and repeatability, and each measurement is tested in the machine direction (MD) (if applicable). The test specimens are prepared from a single film sheet with a length (MD) of 12 cm and a width of 17 cm, which is then cut into individual 1-inch wide (2.54 cm) samples with a thickness of approximately 98 μm. The samples are transferred to the INSTRON tensile testing machine and the tests are performed. The tensile testing machine is prepared according to the manufacturer's instructions, equipped with a 500 N load cell, and calibrated. Attach the appropriate grip and face (INSTRON grip with a 25mm wide, rubber-coated face, model number 2702-032, or equivalent). Mount the sample on a tensile testing machine and analyze it to determine the elongation at break in percent. Measure the actual thickness of the water-soluble film sample before testing, and normalize the mechanical test data from its actual film thickness toward a 76-micron test film to ensure fair comparison between test intervals.
[0084] The dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values listed. Instead, unless otherwise specified, each such dimension is intended to mean both the listed value and the functionally equivalent range encompassing that value. For example, a dimension disclosed as "40 mm" is intended to mean "approximately 40 mm."
Claims
1. A water-soluble unit-dose article comprising a water-soluble film, a treatment composition, and at least one internal compartment, wherein the treatment composition is contained within the at least one internal compartment, the treatment composition is selected from laundry detergent compositions, laundry softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof, and the water-soluble film comprises a water-soluble polymer, and the water-soluble polymer is i) Alginate and, ii) Contains a blend with caseinate polymer, A water-soluble unit-dose article wherein the water-soluble polymer is present in the film at a weight ratio of 50% to 95% and the caseinate polymer is in a weight ratio of 90:10 to 10:
90.
2. The water-soluble unit dose article according to claim 1, wherein the weight ratio of the alginate and the caseinate polymer is 75:25 to 25:
75.
3. The water-soluble unit-dose article according to claim 1 or 2, wherein the caseinate polymer is selected from alkali metal salts of caseinate, preferably sodium caseinate.
4. The water-soluble unit dose article according to any one of claims 1 to 3, wherein the water-soluble polymer is present in the film in an amount of 55% to 90% by weight, more preferably 60% to 80% by weight.
5. The water-soluble unit dose article according to any one of claims 1 to 4, wherein the film comprises a non-aqueous plasticizer, preferably the non-aqueous plasticizer is selected from polyols, sugar alcohols, and mixtures thereof, more preferably selected from glycerol, 1,2-propanediol, trimethylolpropane, dipropylene glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-hydroxymethyl-1,3-propanediol, triethylene glycol, polyethylene glycol, sorbitol, or mixtures thereof, most preferably selected from glycerol, sorbitol, trimethylolpropane, dipropylene glycol, and mixtures thereof, and preferably the film comprises 5% to 50% by weight, preferably 10% to 40% by weight, more preferably 20% to 30% by weight of the non-aqueous plasticizer of the film.
6. The water-soluble unit dose article according to any one of claims 1 to 5, wherein the water-soluble film contains a surfactant in an amount of 0.1% to 5% by weight, preferably 1% to 3% by weight, of the water-soluble film.
7. The water-soluble unit-dose article according to any one of claims 1 to 6, wherein the film, when measured by the method described herein, has a break elongation percentage of about 25% to about 1600%, preferably about 50% to about 1200%, more preferably 75% to 800%.
8. The water-soluble unit-dose article according to any one of claims 1 to 7, wherein the film has a tensile strength (maximum stress at break) of at least 20 MPa.
9. The water-soluble unit-dose article according to any one of claims 1 to 8, wherein the film has a swelling percentage of -15% to 15%, or 0% to 15%, or 5% to 15%, as measured by the method described herein.
10. The water-soluble unit-dose article according to any one of claims 1 to 9, wherein the water-soluble film, when measured by Karl Fischer titration, contains a residual moisture content of at least 4% by weight, more preferably 4% to 15% by weight, and even more preferably 5% to 10% by weight of the film.
11. The water-soluble unit dose article according to any one of claims 1 to 10, wherein the water-soluble film has a thickness of 30 μm to 150 μm, preferably 50 μm to 100 μm, and most preferably 60 μm to 85 μm.
12. A method for producing a film of a water-soluble unit-dose article according to any one of claims 1 to 11, i) A step of dissolving the caseinate polymer, alginate, and any additive in water to form an aqueous solution, A method comprising the steps of: ii) casting the solution obtained from step i) onto a film.
13. The water-soluble unit-dose article according to any one of claims 1 to 11, wherein the processing composition is a laundry detergent composition, preferably a liquid, a powder, or a mixture thereof, preferably a liquid laundry composition.
14. The water-soluble unit-dose article according to any one of claims 1 to 11 or 13, wherein the treatment composition comprises a non-soap surfactant, preferably the non-soap surfactant is selected from an anionic non-soap surfactant, a nonionic surfactant, and a mixture thereof, and preferably the treatment composition comprises 10% to 60% by weight, more preferably 20% to 55% by weight of the non-soap surfactant of the treatment composition.
15. The water-soluble unit-dose article according to any one of claims 1 to 11 or 13 to 14, wherein the treatment composition contains less than 15% by weight, preferably less than 13% by weight, more preferably 1% to 12% by weight, and most preferably 5% to 12% by weight of water.
16. The water-soluble unit-dose article according to any one of claims 1 to 11 or 13 to 15, wherein the treatment composition contains 10% to 40% by weight, preferably 15% to 30% by weight, of a non-aqueous solvent.